Upaya Pengembangan Minat Literasi Kepada Siswa Sekolah Dasar Di Desa Logede - Syiva Levaza; Stella Maris Mbangga Radja; Tara Nabila; Taufik Ardhiansyah; Tarisa Azizah; Taufik Hidayat; Tatasa Diva Cahyakirana; Taufiq Imtiyazurrozin; Ananda Restu Widyaningsih; Yasin Nabil Ajaba; Kuncoro Diharjo (BALE LITERASI, 2022)
Logede Village located in Pejagoan, Kebumen Regency, Central Java. The majority of the people make a living in the agricultural sector and the roof tile industry. Implementation of the KKN Tematik Membangun Desa program based on local village problems and potential. Several aspects that need support, namely in the education sector where learning during the pandemic was carried out using the Distance Learning (PJJ) method. KKN 86 UNS group made a movement in the form of a Literacy Class which aimed to increase reading interest, concentration, and train children to think critically. This literacy class was the result of a discussion between the village apparatus and our group. The implementation method began with an analysis of the information at the Logede Village Elementary School, continued with a survey and visit to the student learning activities then implementation of a literacy class. Concatenation literacy class activities Started with a grand opening to introduce this program to Logede Elementary School students, this event was filled with a drama show and singing performance from KKN UNS 86 group and talented students. Logede Elementary School students look so enthusiastic and happy when participating in this activity. Moreover, when we did concatenation literacy class activities the student felt pleased. The existence of the KKN UNS 86 group hoped that it can increase students' interest in term of reading and introduce the existence of a village library that can be use for reading and learning.